New Concepts of Budo Internalised as a Philosophy of Life - Wojciech J. Cynarski (Philosophies, 2022)
Traditional martial arts continue to be interesting and inspiring to many people around the globe. Some of their contemporary adaptations attract enthusiasts for whom they are especially important. In this article, the author bases his observations on his own long-term participation. The analysis takes into account the influence of the perspectives of Jigoro Kano and several other creators of modern varieties of Japanese budo. It can be concluded that regular, even daily, practice—cultivating martial arts and internalizing its values—co-creates the lifestyle of instructors and advanced students.